Stress, Sleep, Depression and Dietary Intakes Among Low-Income Overweight and Obese Pregnant Women - Chang, Mei-Wei; Brown, Roger; Nitzke, Susan; Smith, Barbara; Eghtedary, Kobra (Maternal and child health journal, 2015)
This study investigated the mediating roles of sleep and depression on the relationships between stress, fat intake, and fruit and vegetable intake among low-income overweight and obese pregnant women by trimesters. Participants (N = 213) completed a self-administered survey including stress (exogenous variable), depression, sleep (mediators), fat intake, and fruit and vegetable intake (endogenous variables). Path analysis was performed to compare mediation effects among pregnant women in each trimester. Consistently across three trimesters, stress was related to depression but not sleep duration, night time sleep disturbance, sleep quality, sleep latency or fat intake. Sleep duration was not associated with depression. Depending on trimester, night time sleep disturbance, sleep quality, and sleep latency were related to depression; night time sleep disturbance and depression affected fat intake; stress influenced fruit and vegetable intake. Sleep duration, sleep disturbance, sleep quality, sleep latency and depression did not mediate the relationships between stress, fat intake, and fruit and vegetable intake in the second and third trimesters. However, depression mediated the relationship between stress and fat intake in the first trimester. Stress management interventions may help low-income overweight and obese pregnant women decrease depressive symptoms and therefore contribute to overall nutritional health.